PEMEROLEHAN KALIMAT BAHASA INDONESIA BERDASARKAN INTONASINYA PADA ANAK USIA 4 â 6 TAHUN - Yalikah, - (Universitas Islam Darul Ulum, 2016)
The study was aimed to determine (1) the form of news sentences based on the intonation, (2) the form of question based on the intonation, and (3) the form of imperative sentences based on the intonation contained in the speech of children at the second Kindergarden PGRI of Plabuhanrejo, District Mantup, Lamongan. The study was a descriptive study. The research data was the Indonesian sentences produced by children in 4-6 years old of the second PGRI of Plabuhanrejo, Mantup. Data was collected using a tape recorder. Data analysis was performed using an interactive model suggested Miles and Huberman. This model consists of: (1) data reduction, (2) data presentation, and (3) conclusion. The results of data analysis showed that children in 4-6 years old at the second kindergarten PGRI of Plabuhanrejo, Mantup has gained the news sentences, interrogative sentence, and imperative sentences. News sentences were found, even in all the data exists. While interrogative sentence and imperative sentences were not gained by the children, because they were a conversation with a friend. From the data found, children in 4-6 years old use interrogative sentence and imperative sentence only rely onÂ the intonation.